Improved prediction of biogas production at Uddebo wastewater treatment plant : Substrate modelling in SIMCA - Gullman, Isak (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2021)
Anaerobic digestion is a complex process, dependent on multiple factors, which can be made more stable and efficient with the help of process models. A more stable process could reduce biogas torching, which increases the amount of renewable energy available for heat- and electricity production and vehicle fuel. Fluctuations in the produced biogas at Uddebo WWTP in Luleå, Sweden, has been observed, where imported industrial waste was suspected to be the cause. The purpose of this master thesis was to increase the predictability of the biogas production at Uddebo WWTP by creating a process model based on historical data. The historical data consisted of quantitative data of the substrates loaded into the anaerobic digestor and biogas collected from the digestor. The results showed that the calculated error between modelled and measured biogas production was <20%, which was considered good. However, due to the demarcation of this report, many variables were ignored in the creation of the model. Further research is therefore a requirement for the model to function properly: The error should be reduced to <10%, This could be done by increasing the period and resolution toinclude and statistically secure fast and seasonal variations. make qualitative modelling easier, i.e., prediction of the biomethane amount in the biogas. The industrial liquid waste storage should be included in the calculation. A more detailed analysis of all substrates is needed to make the comparison between the literature based and measured production more realistic. Expanding the demarcation of the model to also include the environment in the digestor. This could also increase the total amount of biogas produced.